Спекание алмазного поликристаллического композиционного материала в системе Салм.–Si–Pd - Дуда, Т.М.; Шульженко, А.А.; Гаргин, В.Г.; Ткач, В.Н.; Шатохин, В.В.; Белявина, Н.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The influence of rare-earth element activation agent (palladium) on structure deformation
and polycrystall composite, syntered in system C-Si is established. The influence of syntered palladium
oxide on phase structure and composite’s properties is showed.